Changes in carbohydrate content in zucchini fruit (Cucurbita pepo L.) under low temperature stress - Palma, Francisco (Plant science : an international journal of experimental plant biology, 2014)
Copyright © 2013 Elsevier Ireland Ltd. All rights reserved.